The relationship between the Wechsler Memory Scale-Revised scores and whole-brain structure in patients with schizophrenia and healthy individuals. Issue 1 (2nd January 2019) - Hidese, Shinsuke; Ota, Miho; Hori, Hiroaki; Matsuo, Junko; Ishida, Ikki; Hiraishi, Moeko; Teraishi, Toshiya; Hattori, Kotaro; Kunugi, Hiroshi
ABSTRACT: Introduction: The Wechsler Memory Scale (WMS) is a standardised battery for assessing memory functions. We aimed to investigate the relationship between all WMS scores, including subtests, and whole-brain structure in a relatively large sample. Methods: Participants were 93 patients with schizophrenia and 117 healthy individuals, all right-handed and of Japanese ethnicity, and matched for age and sex. Their memory functions were assessed using the WMS-Revised (WMS-R). Their grey and white matter structure was analyzed using voxel-based morphometry and diffusion tensor imaging. Results: Verbal memory score correlated positively with volumes of the left parahippocampal gyrus and hippocampus, while general memory score correlated positively with volumes of the left parahippocampal and fusiform gyri and hippocampus ( p < 0.05, corrected), while there was no correlation with white matter fractional anisotropy values in healthy individuals. No correlation was observed between any WMS-R score and grey or white matter structure in patients. Conclusions: Using whole-brain structural magnetic resonance imaging, we found several significant correlations between WMS-R scores and grey matter volume in the brains of healthy individuals, while no correlation was found in those of patients with schizophrenia.